Near‐Zero Index: Optical Magnetic Mirror for Field Enhancement and Subwavelength Imaging Applications. Issue 12 (18th August 2015) - Choi, Soo Bong; Park, Doo Jae; Byun, Sun Jung; Kyoung, Jisoo; Hwang, Sung Woo
Abstract : Electric field enhancement at the plasmonic nanogap of plasmonic nanostructures is essential for applications such as surface‐enhanced Raman spectroscopy, high‐harmonic generation, molecule sensing, and energy harvesting. Toward achieving higher electric fields, research in the fields of metamaterials and plasmonics has focused on reducing the gap size toward the subnanometer scale. However, the fabrication of extremely small gaps requires complicated techniques, and the resulting tiny scattering cross‐section hinders the efficient use of the enhanced electric field. Here, a completely new approach is proposed to enhance the electric field. Instead of reducing the gap size, it is shown that lowering the refractive index of the substrate very close to zero can increase the electric field by at least an order of magnitude. It is found that the physical origin of such hugely improved field enhancement is the optical magnetic mirror effect at the interface between gap and near‐zero index substrate, which induces phase invariant, near unity reflection. Furthermore, with the help of enhanced electric field, subwavelength slit arrays on the near‐zero‐index substrate are successfully imaged. It is believed that the combination of the near‐zero‐index metamaterials with plasmonic nanogaps can overcome the limitations of current field enhancement technologies. Abstract : Near‐zero‐index (NZI) materials enable the reflected electric field to possess the same phase as the incident field, which is called the optical magnetic mirror effect. In‐phase reflection leads to enhanced electric fields at the subwavelength slit–NZI interface by at least an order of magnitude. This effect increases the imaging resolution of subwavelength structures.